Three-fluorophore FRET enables the analysis of ternary protein association in living plant cells - Glöckner, Nina; Zur Oven-Krockhaus, Sven; Rohr, Leander; Wackenhut, Frank; Burmeister, Moritz; Wanke, Friederike; Holzwart, Eleonore; Meixner, Alfred J.; Wolf, Sebastian; Harter, Klaus (Plants, 2022)
Protein-protein interaction studies provide valuable insights into cellular signaling. Brassinosteroid (BR) signaling is initiated by the hormone-binding receptor Brassinosteroid Insensitive 1 (BRI1) and its co-receptor BRI1 Associated Kinase 1 (BAK1). BRI1 and BAK1 were shown to interact independently with the Receptor-Like Protein 44 (RLP44), which is implicated in BRI1/BAK1-dependent cell wall integrity perception. To demonstrate the proposed complex formation of BRI1, BAK1 and RLP44, we established three-fluorophore intensity-based spectral Förster resonance energy transfer (FRET) and FRET-fluorescence lifetime imaging microscopy (FLIM) for living plant cells. Our evidence indicates that RLP44, BRI1 and BAK1 form a ternary complex in a distinct plasma membrane nanodomain. In contrast, although the immune receptor Flagellin Sensing 2 (FLS2) also forms a heteromer with BAK1, the FLS2/BAK1 complexes are localized to other nanodomains. In conclusion, both three-fluorophore FRET approaches provide a feasible basis for studying the in vivo interaction and sub-compartmentalization of proteins in great detail.
Gesehen am 04.01.2023